THE DEVELOPMENT OF 3D INTERACTIVE MULTIMEDIA ORIENTED SPATIAL VISUALLY ON POLAR AND NONPOLAR COVALENT BONDING MATERIALS - Ilo Isaloka; Kusumawati Dwiningsih (Jurnal Tadris Kimiya, 2020)
Visual-spatial is needed to improve submicroscopic understanding, such as polar and nonpolar covalent bonding materials. Not many 3D interactive multimedia have been developed with visual-spatial orientation. This research aims to produce 3D interactive multimedia with spatial-visual orientation on polar and nonpolar covalent bond materials suitable for use. The research design uses an R&D (Research and Development) research model developed but restricted to a limited trial step. The eligibility criteria include validity (content and construct) and practicality. The validity criteria are based on the results of the validity assessment data from three validators. Practicality criteria are based on the assessment given by three chemistry teachers shortly after the visual-spatial-oriented 3D interactive multimedia trial. Overall data were analyzed descriptive- quantitatively. The results of the study concluded that the developed 3D interactive multimedia meets the eligibility requirements. Each validation indicator in 3D interactive multimedia receives an assessment from the validator with mode (Mo) at least 4 in the score range 1-5 and the percentage of agreement (R) between validators above 75%. The 3D interactive multimedia meets practicality requirements because each indicator receives an assessment from the user students with (Mo) at least 4 in the score range 1-5. The percentage of agreement (R) between user students is above 75%.